Analisis Pendapatan dan Nilai Tambah Selada Organik Kemasan di Desa Baturiti, Kecamatan Baturiti, Kabupaten Tabanan - Utami, Ni Made Astuti Wahyu; Wiguna, I Made Ananda (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2022)
The agricultural sector is one of the main sectors in Indonesia's development. Indonesia is a very important producer of horticultural crops, especially vegetables. Vegetables are a nutritional source of vegetable protein, vitamins, and minerals needed by the human body. The increase in people's need for vegetables continues to increase, so there is an opportunity for lettuce plants. Baturiti Village is one of the villages whose territory is located in the Baturiti District where most of the population works as vegetable farmers. Farmers generally have made economic calculations, but not done in writing and there are still many farmers who have not calculated what level of farming income they cultivate. Therefore it is necessary to analyze the income analysis and added value of lettuce. Based on the calculation results, the income received by the farmers is IDR 22,500,000. The R/C Ratio obtained a result of 5.76. This means that every expenditure of Rp. 1 can provide revenue of Rp. 5.76 with the result R/C is 6.76> 1. This shows that organic Lettuce mustard farming in Baturiti District is profitable and feasible to develop. The break-even point (Break Even Point) obtained from the calculation of BEP units and BEP rupiah for organic lettuce commodities is less than the number of products sold by local farmers and the price is lower than the price set by farmers, therefore farmers have succeeded in selling organic lettuce. by obtaining receipts above the return on capital. The added value obtained from handling packaged organic lettuce is IDR 27,356,667 with a ratio of 58.76 percent. Analysis of added value in postharvest activities of lettuce shows that the greater the added value given to a product, the greater the profit obtained.